New approach for vertical bone regeneration using in situ gelling and sustained BMP-2 releasing poly(phosphazene) hydrogel system on peri-implant site with critical defect in a canine model - Seo, Bo-Bae; Chang, Hae-Im; Choi, Hyuck; Koh, Jeong-Tae; Yun, Kwi-Dug; Lee, Jae-Yeol; Song, Soo-Chang (WILEY, 2018)
An injectable hydrogel system with sustained bone morphogenetic protein 2 (BMP-2) release ability was developed for vertical bone regeneration at peri-implant sites and enhanced osseointegration of dental implants. In three young male beagle dogs, a pair of defects was created on both sides of the mandibular bone. Next, two implants were transplanted into each defect. In situ gelling polymer solutions with or without BMP-2 were applied to cover the implants and mandibular defects. The effects of the in situ gelling and sustained BMP-2 releasing (IGSR) hydrogel system on peri-implant bone regeneration were evaluated by radiologic examination, micro-computed tomography, and histomorphometric analysis. Twelve weeks after the treatment, significant bone generation at the peri-implant site occurred following BMP-2/IGSR hydrogel treatment. Bone volume and mineral density were increased by 1.7- and 1.3-fold, respectively (p<0.01 and 0.05 vs. control, respectively) for the BMP-2/IGSR hydrogel system. And, 0.57-0.31 mm vertical bone generation was observed at the peri-implant site for the BMP-2/IGSR hydrogel system, while rare vertical bone generation occurred in the control group. The BMP-2/IGSR hydrogel system significantly increased bone to implant contact % between induced bone and existing bone (p<0.05 and 0.01 vs. control). These vertical bone regeneration and higher osseointegration levels demonstrated the effectiveness of the BMP-2/IGSR hydrogel system. (c) 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 751-759, 2018.
Keywords: MORPHOGENETIC PROTEIN-2; DELIVERY; RHBMP-2; OSSEOINTEGRATION; AUGMENTATION; COMBINATION; CELLS